Was there voter fraud in the 2021 Peru Presidential Elections? - Raúl Isea; Jesús Isea (Journal of Model Based Research, 2021)
This paper performs a forensic study of the Peru’s presidential election on June 6th, 2021 between Pedro Castillo and Keiko Fujimori, where ex-candidate Keiko Fujimori claimed there had been irregularities. We calculate three p-values that help us determine if there was fraud. The consensus of the results indicates that there was no manipulation of the results.
Keywords: Benford